Willingness to maintain contracts with family doctors among Chinese residents: results from one national cross-sectional study and a meta-analysis of 25 studies - Li, Xinyan; Ye, Jun; Feng, Jing; Chen, Qiaosen; Qu, Ge; Wan, Zhengyi; Lei, Zihui; Ferrier, Adamm; Jiang, Heng; Zheng, Yanling; Gan, Yong (Frontiers in Public Health, 2023)
Background A number of studies have investigated the influencing factors regarding the renewal of contracts associated with Family Doctor Contract Services (FDCS) in different regions of China since it was officially implemented in 2009; however, none of the previous studies have been considered using a nationally representative sample in combination with a meta-analysis. Methods A multistage stratified sampling method was used to investigate participants’ socio-demographic characteristics, health status, understanding, use, and evaluation of the FDCS, and their willingness to renew contracts in Eastern, Central, and Western China from September to November 2021. We searched the PubMed, Ovid Medline, CNKI, VIP, Wanfang, and SinoMed databases to retrieve previous studies related to the willingness of Chinese residents to renew contracts with their family doctor (FD), and a meta-analysis was performed to systematically summarize the willingness to maintain contracts and influencing factors. Results Among 2,394 residents, 2,122 (88.64%) were willing to renew their contracts. The mixed-effect logistic regression model results demonstrated that residents who (1) preferred primary health service institutions, (2) had a better knowledge of FDCS, (3) were more willing to visit primary health service after signing the contract with FDs, (4) were not intending to change FDs, (5) were satisfied with FDCS, and (6) trusted in FDs reported a higher level of willingness to maintain contracts with FDs. Our meta-analysis confirmed that older age, being married, having chronic diseases, choosing primary medical institutions for the first contact, having a good knowledge of FDCS/FDs, being satisfied with FDCS and the medical skills of FDs, and trusting FDs were all positively associated with residents’ willingness to renew contracts (p < 0.05). Conclusion The willingness of consumers to maintain contracts with FDs in China varies in different areas. Giving priority services to groups of high need contributed to an improved rate of renewal. We suggest that in order to continue to increase annual contract renewal, it is necessary to strengthen consumer awareness through effective marketing and continue to work toward meeting consumer expectations, thereby increasing confidence and trust in FDCS.